The Influence of Early Marriage and Parenting Practices on the Nutritional Status of Toddlers in Motui District, North Konawe Regency - Ramadan, Sadrianti; Umi Nurlila, Ratna; Rahmawati, Rahmawati (Waluya The International Science of Health Journal, 2025)
Introduction: Stunting is a major nutritional problem that determines the quality of human resources. The highest prevalence of stunting in the Konawe Islands Regency is at the Langara Health Center at 34.8% in 2022. Then the Bobolio Health Center is at 31.9% and the Lampeapi Health Center is at 32.6%. Poor or inadequate air, sanitation and hygiene conditions can trigger stunting. Method: This type of research is quantitative, Cross Sectional Study design. The research was conducted in February-June 2024 at the Langara, Bobolio and Lampeapi Health Centers, Konawe Islands Regency. The population was all toddlers registered in the working area of ​​the Langara, Bobolio and Lampeapi Health Centers for the period October-December 2023, totaling 1,125 people and a sample of 89 people was obtained. using simple random sampling. Data analysis used the Chi-Square test, Closeness Test and binary logistic regression test. Results: The results of research on the Chi-Square test on drinking water sources with stunting obtained a p value of 0.000, then drinking water management p value 0.000, drinking water quality p value 0.000, φ (0.396), latrine ownership obtained p value 0.001, waste management p value 0.000, waste management p value 0.000, and hygiene p value 0.000. Conclusion : The conclusion is that there is a relationship between early marriage, parenting patterns in feeding practices, personal hygiene, psychosocial parenting and health care practices with the nutritional status of toddlers and the most dominant factor related to the nutritional